The Personality Traits And Career Related Outcomes In The Undergraduate Of Public Universities Of Malaysia - Atif Aziz, Syed Akbar Shah, Syed Akber Hussain Rizvi, Saad Ali (International Journal of Advanced Science and Technology, 2020)
The current study highlights the importance of personality traits and career-related outcomes. The Datacollected and respondent selected from Malaysian undergraduate students of public universities. Thecurrent study applying different statistical techniques to examine the variation of personality traits amongundergraduate students of public universities. This study concludes undergraduate students of publicuniversities are high in extroversion and low in neuroticism. These results indicate that personality traitscan be intervened at the university level. The current study findings have great importance to educatorsand practitioners.